Pendirian Rumah Baca untuk Meningkatkan Literasi Anak pada Masa New Normal di Satuan Pemukiman 1 Transmigrasi Kabupaten Ketapang Kalimantan Barat - Harahap, Saima Putrini R (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2022)
In the new normal period, the face-to-face learning process in schools is not optimal because of the limitation of learning time by changing shifts to avoid crowds. This makes students not fully understand the material presented by the teacher. The purpose of this activity is to improve children's literacy in the new normal period in Settlement Unit 1 (SP 1) Transmigration in Sungai Besar Village, Matan Hilir Selatan District, Ketapang Regency through the establishment of reading houses as a place to assist children's learning after school. This community service activity is carried out by using the observation method and socializing the establishment of reading houses in partnership with PKH (Hope Family Program) companions and the Ketapang District Public Library as suppliers of books or reading materials in the established reading houses. Observation activities were carried out to determine the condition of the student learning process in the new normal period. The socialization activity was carried out to explain the establishment, management and programs that will be carried out in reading houses with the stages of mentoring the establishment of reading houses through PKH assistants on duty at SP1 Sungai Besar Village, introduction to peer tutoring, introduction to literacy culture for local communities. SP 1 Sungai Besar Village, and the recruitment of volunteers and people who care about literacy. The result of this activity is the establishment of a reading house by utilizing unused residents' houses. The manager of the reading house is a Ketapang State Polytechnic student who lives in SP 1 Sungai Besar Village and several students in the area.